Transcriptome and metabolome analyses reveal phenotype formation differences between russet and non-russet apples - Wang, Ziqi; Liu, Shasha; Huo, Wenping; Chen, Min; Zhang, Yugang; Jiang, Shenghui (Frontiers in Plant Science, 2022)
The apple is an economically important fruit, and fruit russeting is not conducive to its appearance. Although studies have examined fruit russeting, its mechanism remains unclear. Two apple strains of the F1 hybrid population derived from ‘Fuji’ and ‘Golden Delicious’ were used in this study. We found that the skin of russet apples was rough and fissured, while that of non-russet apples was smooth and waxy. Chemical staining, LC- and GC-MS showed that both lignin and suberin were increased in russet apple skin. Meanwhile, genes involved in lignin and suberin synthetic pathways were upregulated in russet apple skin. Additionally, we found many differentially expressed genes (DEGs1) involved in hormone biosynthesis and signaling and stress responses in the two apple strains. We found that WRKY13 may influence russeting by regulating lignin synthesis. Our study identified several candidate metabolites and genes, which will provide a good foundation for further research.